Pretreatment of Human Platelets with Plasmin Inhibits Responses toThrombin, but Potentiates Responses to Low Concentrations of Aggregating Agents, Including the Thrombin Receptor Activating Peptide, SFLLRN - Kinlough-Rathbone, R L; Perry, D W; Rand, M L; Packham, M A (Thrombosis and Haemostasis, 1997)
Effects of plasmin on platelets, that influence subsequent responses to aggregating agents, are relevant to attempts to prevent rethrombosis following administration of fibrinolytic agents. We describe plasmin-induced inhibition of platelet responses to thrombin, but potentiation of responses to other aggregating agents. Washed human platelets were labeled with 14C-serotonin, treated for 30 min at 37° C with 0, 0.1 or 0.2 CU/ml of plasmin, followed by aprotinin, washed and resuspended in a Tyrode-albumin solution with apyrase. Incubation with 0.2 CU/ml of plasmin almost completely inhibited thrombin-induced (0.1 U/ml) aggregation, release of 14C-serotonin, and increase in cytosolic [Ca2+]. In contrast, with plasmin-pretreated platelets, aggregation and release of 14C-serotonin were strongly potentiated in response to low concentrations of the thrombin receptor-activating peptide SFLLRN, ADP, platelet-activating factor, collagen, arachidonic acid, the thromboxane mimetic U46619, and the calcium ionophores A23187 and ionomycin. Aspirin or RGDS partially inhibited potentiation. Plasmin-pretreated platelets resuspended in plasma anticoagulated with FPRCH2C1 (PPACK) also showed enhanced responses to aggregating agents other than thrombin. The contrasting effects on responses to thrombin and SFLLRN are noteworthy. Plasmin cleaves GPIIb/IIIa so that it becomes a competent fibrinogen receptor, and binding of 125I-fibrinogen during ADP-induced aggregation was greatly potentiated within 10 s. Potentiation of aggregation by other agonists may be due to increased binding of released fibrinogen. Thus, platelets freed from a thrombus may have increased responsiveness to low concentrations of aggregating agents other than thrombin. These results provide further support for the use of inhibitors of platelet reactions in conjunction with administration of fibrinolytic agents.